Vulneración del principio de rehabilitación social y su incidencia en las personas privadas de libertad de la ciudad de Ibarra. - Cabrera, Omar R. (2022)
The human rights of persons deprived of their main and perhaps the greatest right which is freedom are worthy of a doctrinal and normative study in contrast with the Ecuadorian penitentiary truth, of what is really lived day after day, this study visualizes the existing contradiction between the aspirations inside a prison full of guarantees and respect for the minimum rights, and the truth that persons deprived of freedom have to live inside the prison, where a high rate of overcrowding is observed. Between the State and the prison population there is a legal interaction of particular subjection, which makes the State the guarantor of the minimum rights of these people, who are in a situation of double vulnerability, which explains the desire of the world society to urge governments to safeguard and guarantee through policies that dignify the PPL, and what better way to encourage work within these rehabilitation centers. We get nothing out of hardening a legal system when the problem is not the harshness of the penalty but rather the problem is in trying to change the country with quality education, and generate sources of work that allow people to earn money in a dignified and above all honest way.